Constructing multiple heterojunctions of silver-gallium-gallium oxide on polyetherimide microspheres for lightweight and efficient microwave absorption - Yin, Wan-Rong; Zhao, Kun-Yan; Zhang, Yi-Chuan; Wang, Ming (Composites communications, 2025)
Heterojunctions in conductive or magnetic materials have been well demonstrated to enhance their microwave absorption properties. Herein, polyetherimide (PEI) micro-spheres were first synthesized using an emulsion precipitation method, and plated with silver (Ag) on their surfaces to create PEI-silver (PA) composite micro-particles. Subsequently, liquid metallic gallium (Ga) was coated on the surface of the PA microspheres to obtain the PEI/Ag/Ga (PAG) composite particles. A spherical shell with multiple heterojunctions of Ag-Ga-gallium oxide (Ga2O3) were constructed on the PAG composite micro-particles through an annealing treatment to enhance microwave absorption. Specifically, the PAG45 samples with 45 wt% gallium content demonstrate a minimum reflection loss of - 45.27 dB at a thickness of 2.2 mm and a maximum effective absorption bandwidth of 5.6 GHz at a thickness of 1.4 mm in the intermediate frequency range. The heterogeneous interface of Ag-Ga-Ga2O3, the large specific surface area of the PEI microspheres, and the multiple scattering among the microspheres all contribute to the improved wave-absorbing performance of the composite micro-particles. •Polyetherimide (PEI) microspheres were prepared via an emulsion method.•Multiple heterojunctions are constructed in Ga and Ag coated PEI particles.•The Janus composites have electromagnetic rings and a flat conductive layer.•Polarization loss was enhanced in the Ga2O3-Ga-Ag multiple heterojunctions.•Dielectic and conductive losses were improved in these multiple heterojunctions.